Verruciform xanthoma in a patient with recessive dystrophic epidermolysis bullosa: Case report and literature review. Issue 2 (26th December 2019) - Stephens, Michael; Rubin, Adam I.; Perman, Marissa J.
Abstract: Verruciform xanthoma (VX) is a rare finding thought to be caused by epidermal damage from trauma or inflammation and has been reported in a limited number of patients with recessive dystrophic epidermolysis bullosa (RDEB). Herein, we describe a 20‐year‐old woman with RDEB who developed a large, verrucous, pink plaque on the posterior thigh that was histologically proven to be a VX. We review cases of VX in patients with RDEB and summarize the clinical features, pathophysiology, and management principles.